Implementasi Pembelajaran Bermakna Pada Mata Pelajaran Pendidikan Agama Kristen Dan Budi Pekerti Di Sekolah Menengah Atas - Aang Setiadi (Institut Agama Kristen Negeri (IAKN) Ambon, 2019)
The study of Christian education and ethics or later referred to as PAK in this journal, is a subject that must be followed by all learners who embrace Christianity. The education of Christianity and Ethics is a government-supported education, it can be seen in the 2013 curriculum unit. MR. And Budi ethics are expected to be a pioneer in character education and national values that each graduate can have to answer future challenges. Therefore, the high school, especially the teacher must be able to give the study of PAK that has meaning in the life of each student so that the learning materials that receive can be remembered because it has a deep meaning in Learners.Keyword: Christian education and Ethics, curriculum 2013.